Deconstructing resistance to organizational change: a social representation theory approach. Issue 3 (8th July 2014) - Andersén, Jim; Andersén, Annelie
Abstract : Purpose: – The purpose of this paper is to illustrate how social representation theory (SRT) can be used to understand the concept of resistance to change. SRT is a growing theory in social psychology research. SRT is about how individuals co-construct representations of various objects in different social settings. These social representations govern the attitudes and actions of individuals and groups. In spite of the growing interest in SRT in various fields, no studies have used SRT to understand resistance to organizational change. Design/methodology/approach: – This study reviews the relevant literature on resistance to change and SRT to develop a conceptual framework for understanding resistance from the standpoint of SRT. Findings: – The authors develop a model that illustrates how three interrelated objects, i.e. the organizational process and the pre-and post-change situation, are co-constructed in social contexts. Also, the authors discuss how representations of these objects can co-exist (cognitive polyphasia). Our study illustrates the complexity of resistance to change by deconstructing the concept. Originality/value: – Application of SRT to analyze resistance to organizational change is a novel approach that provides several new insights. For example, where most publications regard advocates of change as sense-givers in the change recipient's sense-making process, the authors argue for a more constructionist approach. Thus, all actors involved in the change process will affect each other and together co-construct the social representations. These social representations govern attitudes to change.